Recurrent Ectopic Pregnancy: Current Perspectives - Petrini A; Spandorfer S (Dove Medical Press, 2020)
Allison Petrini, Steven Spandorfer The Ronald O. Perelman and Claudia Cohen Center for Reproductive Medicine, Weill Cornell Medical College, New York, NY, USACorrespondence: Steven SpandorferThe Ronald O. Perelman and Claudia Cohen Center for Reproductive Medicine, 1305 York Avenue, 6th Floor, New York, NY 10021, USAEmail sdspando@med.cornell.eduAbstract: Ectopic pregnancy represents a potentially life-threatening diagnosis. The risk factors for recurrent ectopic pregnancy have been enumerated but are not yet clearly defined. Understanding which risk factors are perhaps more common may allow providers to counsel and manage patients with a higher level of scrutiny.Keywords: ectopic pregnancy, recurrent ectopic pregnancy, management, risk factors